Marine sponge cyclic peptide theonellamide A disrupts lipid bilayer integrity without forming distinct membrane pores - Espiritu, Rafael Atillo (Animo Repository, 2016)
Theonellamides (TNMs) are antifungal and cytotoxic bicyclic dodecapeptides derived from the marine sponge Theonella sp. These peptides specifically bind to 3β-hydroxysterols, resulting in 1,3-β-d-glucan overproduction and membrane damage in yeasts. The inclusion of cholesterol or ergosterol in phosphatidylcholine membranes significantly enhanced the membrane affinity of theonellamide A (TNM-A) because of its direct interaction with 3β-hydroxyl groups of sterols. To better understand TNM-induced membrane alterations, we investigated the effects of TNM-A on liposome morphology. 31P nuclear magnetic resonance (NMR) and dynamic light scattering (DLS) measurements revealed that the premixing of TNM-A with lipids induced smaller vesicle formation. When giant unilamellar vesicles were incubated with exogenously added TNM-A, confocal micrographs showed dynamic changes in membrane morphology, which were more frequently observed in cholesterol-containing than sterol-free liposomes. In conjunction with our previous data, these results suggest that the membrane action of TNM-A proceeds in two steps: 1) TNM-A binds to the membrane surface through direct interaction with sterols and 2) accumulated TNM-A modifies the local membrane curvature in a concentration-dependent manner, resulting in dramatic membrane morphological changes and membrane disruption. © 2016 Elsevier B.V. All rights reserved.